Could someone please help explain to me how do I would express this questions transformational form and mapping notation? I don't understand what transformational form means......
y=(x+3)^2 - 1
y=(x-2)^2 + 2
y=(x+2)^2 + 1
I think I understand the mapping notation but i'm not sure.......
For the first one this is what I did:
y=(x+3)^2 - 1
When x is 0
y=(0+3)^2-1
y=8
When x is 1
y=(1+3)^2-1
y=15
So the I ploted (0,8) and (1,15) to start and go from x=0 to 4
If anyone could help I would really appreciated it!
y=(x+3)^2 - 1
y=(x-2)^2 + 2
y=(x+2)^2 + 1
I think I understand the mapping notation but i'm not sure.......
For the first one this is what I did:
y=(x+3)^2 - 1
When x is 0
y=(0+3)^2-1
y=8
When x is 1
y=(1+3)^2-1
y=15
So the I ploted (0,8) and (1,15) to start and go from x=0 to 4
If anyone could help I would really appreciated it!